The role of septins on synaptic function and on amyloid precursor protein processing - Ferreira, Catarina B. (2022)
Alzheimer’s disease (AD) is a most devasting form of neurodegenerative disorders, pathologically characterized by neuronal cell degeneration and death, extracellular senile plaques containing amyloid beta (Aβ) and intra-cellular neurofibrillary tangles composed by hyperphosphorylated tau pro-tein. At the molecular and cellular level, AD is associated with a drastic increase of soluble Aβ peptide levels at specific regions in the brain, along-side with deficits in synaptic plasticity, and brain-derived neurotrophic fac-tor (BDNF) signaling impairment. Previous studies have suggested a role for septin (SEPT) protein family members in the cellular processes relevant for AD. The present work thus aimed to elucidate the potential role of pre-synaptic SEPT5 protein and its post-translational modifications in the mo-lecular pathogenesis of AD. Both messenger ribonucleic acid and protein levels of SEPT5 were signifi-cantly decreased in the late stages of AD-related neurofibrillary pathology in well-characterized human post-mortem temporal cortical tissue samples. On the contrary, a significant increase in the phosphorylation of the func-tionally relevant SEPT5 phosphorylation site serine 327 residue (S327) was observed already in the early stages of AD-related neurofibrillary pathol-ogy, but not in the cerebrospinal fluid of patients with mild cognitive im-pairment due to AD. A dependency between SEPT5 S327 phosphorylation status and the effects of SEPT5 on amyloid precursor protein processing and Aβ generation was not observed in the mouse primary cortical neurons transduced with SEPT5 wild type (SEPT5-wt) and its S327 mutants (serine to alanine (S327A) and serine to aspartate (S327D)) lentiviral constructs. Moreover, C57BL/6J mice intrahippocampally injected with lentiviral SEPT5 constructs did not show any cognitive or behavioral deficits, after five to six weeks of overexpression of SEPT5 and its S327 mutants. How-ever, SEPT5 S327 phosphorylation status was linked to changes in short-term plasticity ex vivo at the cornu ammonis (CA) 3-CA1 synapse. Finally, the levels both of the precursor form of BDNF (pro-BDNF) and BDNF in cell culture lysates as well as BDNF levels in cell culture lysates and super-natants were not different in the SEPT5-overexpressing cells. Furthermore, the intracellular domain of tropomyosin-receptor kinase B did not induce SEPT5 phosphorylation at S327. In conclusion, the work presented here underscores the role of SEPT5 and its S327 phosphorylation status, providing important insights into several cellular processes relevant for the pathogenesis of AD.